Automated Bench-Top Device for Evaluation of Air Fine Purification Filters Efficiency - G. G. Smirnov; N. P. Medvedev; A. V. Sen`kin (Проблемы особо опасных инфекций, 2011)
High protective efficiency of filters (fine purification filter-element) used in microbiological laboratories ventilation systems contributes essentially to biological safety provision. Filters are to be tested at bench-top devices prior to application. The existing models of these devices allow to test no more than 8 filters per working day, and require considerable physical efforts. The proposed automated device allows to test 33 filters per working day and decreases considerably workload of the personnel.